Comparison of the effects of Aloe vera gel and coconut oil on the healing of open wounds in rats - Istek, Ozmen; Tanrisever, Murat; Kucukler, Sefa; Karabulut, Burak; Cevik, Aydin (Czech Academy Agricultural Sciences, 2023)
In this study, the effects of Aloe vera gel and coconut oil on wound healing were investigated and compared in rats. Forty-two Wistar albino rats were used during the experiment, in which they were oper-ated on under general anaesthesia to create two full-thickness open skin wounds (created with a 0.5 cm diam-eter punch biopsy apparatus) on both back sides of the median line. A total of 42 rats were divided into three groups of 14 animals each to receive the topical application of Aloe vera gel (AV group -n = 14), coconut oil (CO group -n = 14) and cold cream (CONT group -n = 14). The medical applications were performed twice a day in all the groups. The wound borders were marked on a transparent sheet every day. Afterwards, this sheet was transferred to the millimetre graph paper. On days 0, 7, and 14, the unhealed wound area was measured in all the groups. On days 7 and 14, seven rats in each group were euthanised. Then, skin samples including the intact skin were taken from the wound sites for histopathological and biochemical evaluations. The topical application of Aloe vera gel showed a significant increase in the healing process of the open wounds in terms of the clinical evaluation, histopathological and biochemical data averages when compared with the coconut oil and cold cream groups of rats (P < 0.05). The results obtained in the present study demonstrate that Aloe vera gel may provide a good alternative for the treatment of open wounds.
Keywords: Aloe vera gel; coconut oil; rat; wound healing of animals